Learners' experiences of teachers' aggression in a secondary school in Gauteng, South Africa - Aneshree Naicker; Chris Myburgh; Marie Poggenpoel (AOSIS, 2014)
Background: Research shows that one third of all persons in South Africa have been exposed to one or more types of aggression. It has been observed that learners frequently experience aggression from teachers in the secondary school environment, which has a negative effect on their experience of general wellbeing and mental health. Objectives: The objectives set for this research were to explore and describe learners' experiences regarding teachers' aggression toward them and to formulate guidelines for learners and teachers to facilitate their mental health. Method: The population consisted of school learners at a secondary school. Inclusion criteria for sampling were that participants should be grade 11 and 12 learners, between 16 and 18 years of age and should have experienced aggression from teachers in the school. A purposive sample was taken of learners who complied with the inclusion criteria. Data were collected by means of four in-depth phenomenological interviews, 88 naïve sketches, observation and field notes. One central question was posed to the secondary school learners: 'What are your experiences of teacher aggression toward you in your schooling environment?' Open coding was used for data analysis. Measures to ensure trustworthiness were applied to ensure the rigour of the research. Ethical principles were adhered to throughout the research process. Results: The secondary school learners were belittled, as well as emotionally and verbally abused. They also experienced fear and anger. Guidelines were derived from these findings for learners and teachers. Conclusion: This research found that learners experience aggression in their school environment and need support to facilitate their mental health. Agtergrond: Navorsing toon dat een derde van alle mense in Suid-Afrika al aan een of ander vorm van geweld blootgestel is. Daar is waargeneem dat leerders dikwels aggressie by onderwysers in die sekondêre skool beleef, wat 'n negatiewe uitwerking op hul algemene welsyn en geestelike gesondheid het. Doelstellings: Die doelstellings vir hierdie navorsing was om leerders se belewing van onderwysers se aggressie te verken en om riglyne te formuleer vir leerders en onderwysers om hulle geestesgesondheid te fasiliteer. Metode: Die populasie het uit leerders by 'n sekondêre skool bestaan. Die kriteria vir insluiting by die steekproef was dat deelnemers in graad 11 of 12 moet wees, tussen 16 en 18 jaar oud, en moes aggressie by onderwysers aan die skool beleef het. 'n Doelgerigte steekproef van leerders wie aan die insluitingskriteria voldoen, is geneem. Data is ingesamel deur middel van vier diepgaande fenomenologiese onderhoude, 88 naïewe sketse, waarneming en veldnotas. Een sentrale vraag is aan die sekondêre skool leerders gestel: 'Wat is jou belewing van onderwysers se aggressie teenoor jou in jou skoolomgewing?'. Oop kodering is gebruik om die ingesamelde data te analiseer. Maatreëls om vertrouenswaardigheid te verseker is toegepas om die wetenskaplikheid van die navorsing te verseker. Etiese beginsels is dwarsdeur die navorsingsproses toegepas. Resultate: Die sekondêre skool leerders beleef dat hulle verneder word, asook emosioneel en verbaal mishandel word. Hulle beleef ook vrees en woede. Riglyne vir leerders en onderwysers is uit hierdie bevindinge afgelei. Gevolgtrekkings: Hierdie navorsing het bevind dat leerders aggressie in hul skoolomgewing beleef en ondersteuning benodig om hul geestesgesondheid te fasiliteer.